2008
DOI: 10.1681/asn.2008010011
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Vitamin D Receptor Produces Polyuria by Increasing Thirst

Abstract: Vitamin D receptor (VDR)-null mice develop polyuria, but the underlying mechanism remains unknown. In this study, we investigated the relationship between vitamin D and homeostasis of water and electrolytes. VDR-null mice had polyuria, but the urine osmolarity was normal as a result of high salt excretion. The urinary responses to water restriction and to vasopressin were similar between wild-type and VDR-null mice, suggesting intact fluid-handling capacity in VDR-null mice. Compared with wild-type mice, howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 39 publications
1
22
0
1
Order By: Relevance
“…As expected, plasma and urinary aldosterone levels are also markedly elevated in VDR knockout mice [71]. Moreover, renin expression in the brain is also up-regulated in VDR-null mice, leading to activation of the local RAS in the brain, which is mostly responsible for the overdrinking and polyuric phenotypes seen in the mutant mice [72].…”
Section: Vitamin D Hormone As a Negative Endocrine Regulator Of The Rsupporting
confidence: 72%
“…As expected, plasma and urinary aldosterone levels are also markedly elevated in VDR knockout mice [71]. Moreover, renin expression in the brain is also up-regulated in VDR-null mice, leading to activation of the local RAS in the brain, which is mostly responsible for the overdrinking and polyuric phenotypes seen in the mutant mice [72].…”
Section: Vitamin D Hormone As a Negative Endocrine Regulator Of The Rsupporting
confidence: 72%
“…38 Here our immunostaining data showed that renin is highly induced by losartan in the blood vessel walls in the left ventricle, and this finding is consistent with our previous report that renin expression was detected in the vasculatures in mouse brain. 39 The exact role of endothelial renin deserves further investigations.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, using similar mice, reduction of renin-angiotensin activity in paraventricular nucleus with inhibition of thirst was achieved following vitamin D analogs injection. The authors concluded that polydipsia and polyuria may be caused by a lack of vitamin D [150]. Nocturnal polyuria had been reported in normal children [152,153] and children with SCA who had NE and was considered a pathogenic factor [18,41,51,52].…”
Section: Vitamin Dmentioning
confidence: 99%
“…Vitamin D receptor knockout mice that had normal renal function were observed to develop polyuria, as a result of increased water intake [150]. The latter was due to renin up regulation leading to an increased production of angiotensin II [151].…”
Section: Vitamin Dmentioning
confidence: 99%